3D skin length deformation of lower body during knee joint flexion for the practical application of functional sportswear. (May 2015) - Choi, Jiyoung; Hong, Kyunghi
Abstract: With the advent of 3D technology in the design process, a tremendous amount of scanned data is available. However, it is difficult to trace the quantitative skin deformation of a designated location on the 3D body surface data during movement. Without identical landmarks or reflective markers, tracing the same reference points on the different body postures is not easy because of the complex shape change of the body. To find the least deformed location on the body, which is regarded as the optimal position of seams for the various lengths of functional compression pants, landmarks were directly marked on the skin of six subjects and scanned during knee joint flexion. Lines of non-extension (LoNE) and maximum stretch (LoMS) were searched for, both by tracing landmarks and newly drawn guidelines based on ratio division in various directions. Considering the waist as the anchoring position of the pants, holistic changes were quantified and visualized from the waistline in lengthwise and curvilinear deformation along the dermatomes of the lower body for various lengths of pants. Widthwise and unit area skin deformation data of the skin were also provided as guidelines for further use such as streamlined pants or design of other local wearing devices. Highlights: Visualization of skin deformation including lines of non-extension was provided. Skin deformation along the dermatome directions of lower body was investigated. Optimal positions of seam for the various lengths of functional pants were suggested. Unit area deformation can be used for the attachment of various wearing devices.